Theoretical lifetimes and Stark broadening parameters for visible-infrared spectral lines of V i in Arcturus. Issue 3 (13th November 2021) - Isidoro-García, L; de Andrés-García, I; Moreno-Conde, D; Colón, C
ABSTRACT: In this work, the Stark broadening parameters (line widths and line shifts) of 114 visible-infrared spectral lines of neutral vanadium (V i ) have been calculated. As in a previous work devoted to their spectral lines in the Ultraviolet (UV)-blue range, these parameters have been calculated using the Griem's semi-empirical formula and the Cowan code for the calculation of the necessary matrix elements. In addition to their astrophysical interest (the majority of the analysed spectral lines have been detected in Arcturus, in the metal-poor star HD 84937 and in the Sun), these parameters are also relevant in the analysis of plasmas generated in industrial processes in Laser Shock Processes treatments of Ti-6Al-4V type samples.